Avaliação das práticas de criopreservação sobre espermatozoides de jumento (Equus asinus). - Monteiro, Rodrigo Alves (2020)
The most reproduction techniques used in donkeys are adaptations on other species, the equine are the base for these practices. Therefore, the development in practice of cryopreservation directed by asses is necessary. Based this, the aim in this study was assess the perform on removing the seminal plasma (SP) and evaluate methods of freezing semen in donkeys (Equus asinus), establish news protocols for the field routine is important. Were evaluated two methods of removal SP, centrifugation and filtration, and the freezing systems, automated and conventional. Three jackass, healthy, were used. By collections, was used artificial vagina method, sets are six ejaculates for each jackass. After the colections and free gel, the semen was divided in two parts, submitted to commercial membrane filter (SpermFilter®), another part subjected by centrifugation (600xg for 10 minutes). In order to freezing methods, the conventional system used (refrigerator 5 °C/ ramp in storyfoam box) and the automated system (TK-3000®, curve P2S2) were used. Thus were groups formed: automated centrifuged (MC), automaed filtrate (MF), conventional centrifuged (RC) and completed conventional filtrate (RF). Subjective analyzes were performed on fresh semen (motility, vigor, concentration, pH, morphology and integrity of membrane). The data were submitted to statistics evaluation (normality test, ANOVA, post test Turkey with 5% significance). The animals were evaluated individually and after finding that there was no difference between individuals, the data were grouped by formed experimental group. It was found that the groups submitted to the filtration technique showed greater sperm recovery (P<0.05) than the centrifuged ones. Found that groups submitted to the filtration technique showed great recovery (P<0.05) than the centrifugation groups. Other parameters (sperm morphology, membrane integrity and functionality) there was no difference (P>0.05) between the experimental groups. It was observed that the RF group had lower (P<0.05) progressive motility and curvilinear speed than the other groups tested. In conclusion, the centrifugation is the best technique to remove SP in donkeys. The method automated freezing, in donkeys, proved to be safer and more constant in reducing the temperature, the conventional method can be an alternative since performed on the fast curve.